2023
DOI: 10.3389/fpsyg.2023.1190800
|View full text |Cite
|
Sign up to set email alerts
|

The overall and domain-specific quality of life of Chinese community-dwelling older adults: the role of intrinsic capacity and disease burden

Xiuhua Hu,
Jian Ruan,
Weibin Zhang
et al.

Abstract: ObjectiveThis study aimed to investigate the impact of the different domains of intrinsic capacity (IC) and chronic disease burden on health-related quality of life (HRQoL) and domain-specific HRQoL in Chinese community-dwelling older adults.DesignA cross-sectional observational study of a community-based cohort.ParticipantsWe evaluated Chinese older adults (n = 429, mean age, 72.91 ± 7.014 years; female proportion, 57.30%).MeasurementsIC contains five domains, namely locomotion, vitality, cognition, psycholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
(88 reference statements)
0
0
0
Order By: Relevance
“…Sensorial frailty mainly affects the domains of senses, and mobility affects the domains of independent living and pain. [ 42 ] In this study, our results indicated that both sensorial and mobility frailty had a significant influence on overall and domain-specific cognitive function, even if the influence of mobility frailty was stronger than that of sensorial frailty. Thus, in order to unify the dimensions of frailty and IC, we suggest that sensory and mobility dimensions of IC should be integrated into the physical frailty phenotype to facilitate clinical research and healthcare, and improve the sensitivity of physical frailty screening instrument.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Sensorial frailty mainly affects the domains of senses, and mobility affects the domains of independent living and pain. [ 42 ] In this study, our results indicated that both sensorial and mobility frailty had a significant influence on overall and domain-specific cognitive function, even if the influence of mobility frailty was stronger than that of sensorial frailty. Thus, in order to unify the dimensions of frailty and IC, we suggest that sensory and mobility dimensions of IC should be integrated into the physical frailty phenotype to facilitate clinical research and healthcare, and improve the sensitivity of physical frailty screening instrument.…”
Section: Discussionmentioning
confidence: 56%
“…Although vitality decline had an extensive negative impact on health-related quality of life, including overall health-related quality of life, the domains of senses and pain in the physical dimension, and the domains of mental health and relationships in the psychosocial dimension after adjustment for demographic, health-related, and psychological confounders, [ 42 ] we did not find an adverse impact of vitality on overall and domain-specific cognitive function. The impact of vitality on cognitive function needs to be investigated using a longitudinal cohort with a large sample and validated assessment tools of vitality.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations